Investigating the Differences Between Mentorship, Advanced Degrees, and Career Advancement Among Mid-Level Black Women Administrators in Higher Education within the Southeastern Region of the United States - Story, Parris S. (My University, 2026)
The purpose of this study was to examine differences in career advancement among mid-level African American women administrators in higher education based on educational attainment and institutional type, and to assess the extent to which mentoring predicts career advancement. Data were collected from mid-level African American women employed at colleges and universities in the southeastern region of the United States including, Alabama, Georgia, Florida, Mississippi, North Carolina, South Carolina, and Tennessee. A quantitative, non-experimental design was employed, using a survey instrument to collect data on participants’ educational attainment, years of professional experience, position classification, institution type, mentoring experiences, and perceptions of career advancement. Descriptive statistics, one-way analysis of variance (ANOVA), and simple linear regression were used to analyze the data. The findings indicated no statistically significant differences in years of professional experience and academic degree attainment. However, statistically significant differences in career advancement opportunities were found based on institutional type. In addition, mentoring was not a statistically significant predictor of career advancement. These findings suggest that, while mentoring is often emphasized as a key support resource, broader structural and organizational factors may play a more influential role in shaping career advancement among mid-level African American women administrators in higher education. The findings have important implications for institutional leaders seeking to support career advancement of mid-level African American women administrators and highlight the need for future research that incorporates qualitative or mixed methods approaches to better understand the lived experiences underlying these outcomes.
Keywords: College administrators; African American studies; Women college administrators; African American women college administrators; Career development; Education, Higher; Educational leadership; Mentoring in education; Dissertations, Academic